Pengembangan Media Pembelajaran Interaktif Berbasis Augmented Reality untuk Meningkatkan Pemahaman Konsep IPA - Anggriyani Uno, Winda (Almeera Education, 2024)
This study aims to develop interactive learning media based on Augmented Reality (AR) to enhance the understanding of Science concepts among students at SDN 10 Tilamuta. The AR-based learning media is designed to offer a more engaging and interactive learning experience, allowing students to view and interact with three-dimensional science objects. The research methodology employed is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data were collected through observations, interviews, and tests of students' understanding before and after the use of the media. The results indicate that the use of AR learning media significantly improves students' comprehension of science concepts. Students’ responses to the media were also highly positive, reflecting increased motivation and engagement in the learning process. This study is expected to serve as a reference for the development of other learning media utilizing AR technology to enhance the effectiveness of science education in elementary schools.